2017
DOI: 10.1080/03007995.2017.1397506
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of patients with type 2 diabetes mellitus to medications: the role of risk preferences

Abstract: Risk-seeking patients are less adherent to OHA medications. Identifying these patients may enable practitioners to proactively tailor strategies to improve their adherence and health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Using lottery choice tasks, Simon-Tuval et al demonstrated that risk-seeking patients with type 2 diabetes adhere less to selfcare behavior and medications. 8,9 We previously showed that patients with diabetes who were risk-seeking in judging hypothetical lotteries were prone to developing complications. 7 Although the method for estimating risk preferences using the maximum price that an individual's willing to pay for a lottery ticket has been proved in economics, [13][14][15] the participants of these studies were usually healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using lottery choice tasks, Simon-Tuval et al demonstrated that risk-seeking patients with type 2 diabetes adhere less to selfcare behavior and medications. 8,9 We previously showed that patients with diabetes who were risk-seeking in judging hypothetical lotteries were prone to developing complications. 7 Although the method for estimating risk preferences using the maximum price that an individual's willing to pay for a lottery ticket has been proved in economics, [13][14][15] the participants of these studies were usually healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…The findings are consistent with those reported by Simon-Tuval et al indicating using hypothetical lotteries that risk-seeking preferences are significantly associated with failure in self-management and the medication nonadherence. 8,9 However, because we used an open pricing method in the questionnaires, there were varied responses. Some patients indicated that they would pay more for a lottery ticket than they could win, which seemed irrational.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, social compliance constitutes a behavior which is likely to resonate with individual time and risk preferences. This idea is supported by evidence of health-related contexts, highlighting that patience positively a↵ects the adherence to physical activity advice (Van Der Pol et al, 2017), whereas more risk tolerant subjects are less likely to adhere to medications (Simon-Tuval et al, 2018). Compliance also requires from citizens that they trust the appropriateness of the measures and the reliability of the provided information.…”
Section: Introductionmentioning
confidence: 97%
“…Most of the RP published literature focused on health behaviors that are driven to prevent the development of infectious diseases, such as AIDS [20], and specific cancers [21, 22] and facilitate the diagnosis of diabetes mellitus (DM) in healthy (at risk) individuals [2325]. Two studies assessed RP in adult patients who were already diagnosed with type 2 DM, and both studies found an association between the degree of risk and adherence to medication [24, 25]. There is limited RP-literature published in the field of rheumatic diseases.…”
Section: Introductionmentioning
confidence: 99%